2022
DOI: 10.1128/spectrum.02669-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the SARS-CoV-2 Pandemic on the Prevalence and Incidence of Gastrointestinal Viruses in Children up to Five Years Old: a Retrospective Cohort Study

Abstract: Our original article contains an analysis of the impact of the measures applied against SARS-CoV-2 on the prevalence and incidence of GV in children. The small number of studies published to date that analyze the impact of these measures individually on each of the GV makes our study of great interest at this time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…Surveillance Study Team also reported a similar seasonal pattern. 21 Some similar evidence has been found in several national studies, such as in Spain, 22 the Czech Republic, 23 Germany, 24 Norway, 25 England, 26 and the United States. 27 In autumn and winter, the temperature is relatively low and may influence transmissibility, host susceptibility, and the resistance of norovirus to environmental conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Surveillance Study Team also reported a similar seasonal pattern. 21 Some similar evidence has been found in several national studies, such as in Spain, 22 the Czech Republic, 23 Germany, 24 Norway, 25 England, 26 and the United States. 27 In autumn and winter, the temperature is relatively low and may influence transmissibility, host susceptibility, and the resistance of norovirus to environmental conditions.…”
Section: Discussionsupporting
confidence: 75%
“…Samples were collected more than two years prior to analysis, which could compromise their integrity [ 53 ]. The study setting might have experienced a further change in enteropathogen burden since 2018 in part due to the coronavirus disease 2019 (COVID-19) pandemic as has been observed elsewhere [ 54 , 55 ]. However, this does not invalidate the hypotheses generated by the findings regarding enteropathogen dynamics, but rather suggests that continuous surveillance is critical for adapting and maximizing diarrheal illness prevention.…”
Section: Discussionmentioning
confidence: 99%
“…However, in 2021 there was a surge of RVA cases in these countries. Like RVA, a decrease in cases of norovirus GII, sapovirus, adenovirus 40/41 and astrovirus was reported in 2020 in Spain 8 and Korea 9 compared to previous years. However, this decrease in virus detecMon has been followed by remarkable outbreaks in 2021 5,10 .…”
Section: Introduc-onmentioning
confidence: 93%
“…Of the 130 RVA posiMve detected during the study, 87 (66.9%) and 70 (53.8%) successively 207 sequenced in the VP7 and VP4 segment, respecMvely. The years 2019, 2020 and 2021 were 208 predominated by the G3P [8] genotype (n=48, 80.0%). In 2022, we observed replacement of 209 the G3P [8] genotype with mulMple genotypes: G2P [4] (n=2), G9P [8] (n=10), and G9P [4]…”
Section: Rva Genotypes and Vaccina-on Status Of Posi-ve Cases 206mentioning
confidence: 99%
See 1 more Smart Citation